2020 BioImage Analysis Survey: Community experiences and needs for the future. (12th November 2022) - Jamali, Nasim; Dobson, Ellen T. A.; Eliceiri, Kevin W.; Carpenter, Anne E.; Cimini, Beth A.
Abstract: In this paper, we summarize a global survey of 484 participants of the imaging community, conducted in 2020 through the NIH-funded Center for Open Bioimage Analysis (COBA). This 23-question survey covered experience with image analysis, scientific background and demographics, and views and requests from different members of the imaging community. Through open-ended questions, we asked the community to provide feedback for the open-source tool developers and tool user groups. The community's requests for tool developers include general improvement of tool documentation and easy-to-follow tutorials. Respondents encourage tool users to follow the best practice guidelines for imaging and ask their image analysis questions on the Scientific Community Image Forum (forum.image.sc ). We analyzed the community's preferred method of learning based on level of computational proficiency and work description. In general, written step-by-step and video tutorials are preferred methods of learning by the community, followed by interactive webinars and office hours with an expert. There is also enthusiasm for a centralized online location for existing educational resources. The survey results will help the community, especially developers, trainers, and organizations like COBA, decide how to structure and prioritize their efforts.